The utility of automated volume analysis of renal stones before and after shockwave lithotripsy treatment - Cui, HW; Tan, TK; Christiansen, FE; Osther, PJS; Turney, BW (Springer, 2020)
This study aimed to evaluate the additional utility of an automated method of estimating volume for stones being treated with shockwave lithotripsy (SWL) using computed tomography (CT) images compared to manual measurement. Utility was assessed as the ability to accurately measure stone burden before and after SWL treatment, and whether stone volume is a better predictor of SWL outcome than stone diameter. 72 patients treated with SWL for a renal stone with available CT scans before and after treatment were included. Stone axes measurement and volume estimation using ellipsoid equations were compared to volume estimation using software using CT textural analysis (CTTA) of stone images. There was strong correlation (r > 0.8) between manual and CTTA estimated stone volume. CTTA measured stone volume showed the highest predictive value (r2 = 0.217) for successful SWL outcome on binary logistic regression analysis. Three cases that were originally classified as 'stone-free with clinically insignificant residual fragments' based on manual axis measurements actually had a larger stone volume based on CTTA estimation than the smallest fragments remaining for cases with an outcome of 'not stone-free'. This study suggests objective measurement of total stone volume could improve estimation of stone burden before and after treatment. Current definitions of stone-free status based on manual measurements of residual fragment sizes are not accurate and may underestimate remaining stone burden after treatment. Future studies reporting on the efficacy of different stone treatments should consider using objective stone volume measurements based on CT image analysis as an outcome measure of stone-free state.